A Framework for Understanding the Influence of Isomorphic Pressures on Governance of Disaster Risks. (2018) - Toinpre, O.; Mackee, J.; Gajendran, T.
Abstract: The task of reducing disaster risks poses enormous challenges for international and local non-governmental organizations despite the immense assistance offered in reducing disaster risks and cushioning the effect of disasters. Among other issues responsible for the setback experienced is that of institutional constraints. 'Institutions' act as a fulcrum for achieving social norms that shape behaviour and actions within society via rules, professional ethics, standards, policies, regulations etc. Government establishments in the same organizational field - particularly those recognized to deliver public goods and services for disaster risk reduction often experience institutional constraints such as lack of clear policies and mandates to guide government institutions, lack of coordination between institutions, inadequacy in the required human capacity in public sector etc. These constraints often contribute to increased societal risk conditions. Where institutions are elements of governance, framing them also becomes a simultaneous attempt to manage risks to society. An overwhelming body of existing organizational behaviour literature affirms that organizations adopt practices or behave in a certain manner to gain access to resources and legitimacy for survival including under uncertain or complex circumstances when subjected to institutional pressures. Such pressures influence operational and strategic arrangements and has been discussed from a private sector organizations perspective. Against this background, little attention has been given to influence of institutional pressures on public sector organizations and scarcely from a disaster risk reduction perspective. The aim of this paper is to investigate the role of governance and influences of institutional pressures on public sector organizations from a disaster risk reduction perspective. This is achieved through reviewing literature on institutional theory to provide an understanding on the concept of institutional isomorphism and its effect on key issues such as goal ambiguity, professionalism and structuration as well as technical uncertainty. The implication for practitioners is that it offers background knowledge required for key players and professionals to design appropriate response strategies to isomorphic pressures to support institutional sustainability, encourage homogeneity for effective DRR delivery and fills the knowledge gap presented for further research.